The Use of ELSA Speak as a Mobile-Assisted Language Learning (MALL) towards EFL Students Pronunciation - Sholekhah, Miratu Fitria; Fakhrurriana, Ria (Universitas Siliwangi, 2023)
This study analyses how students' pronunciation can be improved through the use of the ELSA Speak as a Mobile-Assisted Language Learning (MALL) tool. ELSA stands for English Language Speech Assistant. The speech recognition function of ELSA Speak is powered by artificial intelligence (AI), and it provides users with feedback to help them improve their pronunciation, which improves their ability to speak English. This study investigates the influence and potential of the ELSA Speak application on the acquisition of pronunciation by employing a qualitative research method and a strategy that relies on library research. The findings highlight the significance of having an excellent content design, an efficient pedagogical and instructional design, gamified learning elements, automatic voice recognition technology, a secure learning environment, and individualised digital feedback. The findings of the study indicate that there is considerably significant potential for the ELSA Speak application to help students improve their pronunciation skills. The consequences of this research emphasize the necessity of utilising cutting-edge mobile applications for language learning and highlight the possible benefits for students interested in improving their pronunciation proficiency. Keywords: Elsa Speak; Mobile-Assisted Language Learning; Students' Pronunciation; Pronunciation Improvement.